ln(1+x)+ln(x-2)=ln(4)

Simple and best practice solution for ln(1+x)+ln(x-2)=ln(4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(1+x)+ln(x-2)=ln(4) equation:


Simplifying
ln(1 + x) + ln(x + -2) = ln(4)
(1 * ln + x * ln) + ln(x + -2) = ln(4)
(1ln + lnx) + ln(x + -2) = ln(4)

Reorder the terms:
1ln + lnx + ln(-2 + x) = ln(4)
1ln + lnx + (-2 * ln + x * ln) = ln(4)
1ln + lnx + (-2ln + lnx) = ln(4)

Reorder the terms:
1ln + -2ln + lnx + lnx = ln(4)

Combine like terms: 1ln + -2ln = -1ln
-1ln + lnx + lnx = ln(4)

Combine like terms: lnx + lnx = 2lnx
-1ln + 2lnx = ln(4)

Reorder the terms for easier multiplication:
-1ln + 2lnx = 4ln

Solving
-1ln + 2lnx = 4ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-4ln' to each side of the equation.
-1ln + -4ln + 2lnx = 4ln + -4ln

Combine like terms: -1ln + -4ln = -5ln
-5ln + 2lnx = 4ln + -4ln

Combine like terms: 4ln + -4ln = 0
-5ln + 2lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-5 + 2x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-5 + 2x)' equal to zero and attempt to solve: Simplifying -5 + 2x = 0 Solving -5 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = 0 + 5 2x = 0 + 5 Combine like terms: 0 + 5 = 5 2x = 5 Add '-2x' to each side of the equation. 2x + -2x = 5 + -2x Combine like terms: 2x + -2x = 0 0 = 5 + -2x Simplifying 0 = 5 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| ln(a)=2.813585093 | | 5xy-3x-4y-1=0 | | ln(3+x)+ln(6-x)=ln(15) | | 2x+35=12x-5 | | 2kx+9=4x+kx | | -(9-c)= | | 3/5=2000 | | x+0.05x=168 | | c=28/3x15 | | x^2+4x+4-9=0 | | c=28/3m | | x+3x+x-12=180 | | x+3x+x-15=180 | | x+3x+(x-12)=180 | | 3e+1=10p | | 5.4/.12 | | 54./.12 | | .7x-.3=.6x+4 | | tgx=0.0042 | | -4*96/100 | | 9(7x-1)=7(7x+1)+390 | | 4sin(x/2)cos(x/2) | | 11*(-11)= | | 25a^4-10a^2b^2+b^4=0 | | 3x+22-2x=9+4x-5 | | 63-7=36x+560 | | (x^2-3x+1)(x^2+3x-3)=5 | | 8x^2+117x-45=0 | | 272000/600 | | y^1=8y^2+91 | | 13-w=1-4w | | 4x^8-4ax^4+a^2=0 |

Equations solver categories